Surface Erosion Impact in Upper Serang Watershed Kemusu Municiaplity Boyolali District Centra Java - Kuswaji Dwi Priyono (Universitas Muhammadiyah Surakarta, 1990)
The aim of this reseach are two fold. The first it to clasify and evaluate the surface crosivity and the second is to map the erosivity hazard. The final yield is a map of ... - ... in 1 : 50.000. the classification of surface erosivity is based on top soil loss maximum using the Universal Soil Loss Equation (USLE) of Wischmeir and Smith Method; that is executed on every unit of land. Land unit is detected through interpretation of false colour I.R. air photograph images, shot in 1981/ 1982, scale 1 : 50.000. The classification fields the following data : erosity intensity is 6,687.5 hm (26.78 percent) is ultimate low; 2,962.5 hm (11.86 percent) is low; 5,025.0 hm (20.12 percent) is medium 5,025.0 hm (20.12 percent) is medium 287.5 hm (1.15 percent) is high, while the in habited area has 4,637 hm (18.57 percent) or classified as a very low intensity.